2020
DOI: 10.1002/pld3.275
|View full text |Cite
|
Sign up to set email alerts
|

High affinity Na+ transport by wheat HKT1;5 is blocked by K+

Abstract: The wheat sodium transporters TmHKT1;5‐A and TaHKT1;5‐D are encoded by genes underlying the major shoot Na+ exclusion loci Nax2 and Kna1 from Triticum monococcum (Tm) and Triticum aestivum (Ta), respectively. In contrast to HKT2 transporters that have been shown to exhibit high affinity K+‐dependent Na+ transport, HKT1 proteins have, with one exception, only been shown to catalyze low affinity Na+ transport and no K+ transport. Here, using heterologous expression in Xenopus laevis oocytes we uncover a novel pr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…The estimated broad-sense heritability for wheat salinity tolerance in the present study was 0.51 (SDS), indicating a significant interaction between genotypes and environments with genotypes contributing half of the phenotypic variation. The exclusion of Na + ions is associated with salinity tolerance in wheat (Davenport et al 2005;Genc et al 2010;Naeem et al 2020;Xu et al 2020). Our preliminary test of shoot Na + concentration, from one of the tank trials, showed that most of the genotypes had a relatively low Na + concentration in their shoots.…”
Section: Salinity Tolerance Of Wheat Accessionsmentioning
confidence: 82%
“…The estimated broad-sense heritability for wheat salinity tolerance in the present study was 0.51 (SDS), indicating a significant interaction between genotypes and environments with genotypes contributing half of the phenotypic variation. The exclusion of Na + ions is associated with salinity tolerance in wheat (Davenport et al 2005;Genc et al 2010;Naeem et al 2020;Xu et al 2020). Our preliminary test of shoot Na + concentration, from one of the tank trials, showed that most of the genotypes had a relatively low Na + concentration in their shoots.…”
Section: Salinity Tolerance Of Wheat Accessionsmentioning
confidence: 82%
“…However, the high-affinity transport function becomes inactive when the external K + concentration surpasses that of external Na + . Additionally, the low-affinity transport function is also impeded by the presence of an external potassium ions supply (K + ) [ 48 ]. In this study, it is evident that MeHKT1 transgenic Arabidopsis accumulates higher levels of K + in its shoots in comparison to the WT when subjected to low K + conditions (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…Research on NRT1.1 gene-mediated nitrate uptake and transport in apples will be beneficial for improving nitrogen fertilizer utilization [5,6,39,[45][46][47]. Moreover, recent studies have found that the nitrate transporter protein NRT1.1 plays an important role in various environmental stresses [32,37,[48][49][50][51][52][53][54].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the deepening of GUS staining and upregulation of the expression level GUS under salt stress treatment indicated that MdNRT1.1 reduced salt tolerance in plants (Figure S4). The MDA content of MdNRT1.1, the increase in relative conductivity, and the staining of DAB and NBT indicated that the plant tissues in MdNRT1.1-OX were severely damaged (Figure 6D-G), which may have been due to the fact that NRT1.1 promoted the transport of Na + from the roots to the shoots, leading to an attack of reactive oxygen species on the biological membranes in the plants, resulting in loss of membrane permeability function and disruption of photosynthesis and respiratory metabolism [37,38,[48][49][50][51][52][53][54]. As salt stress mainly causes osmotic stress and peroxide accumulation in plants, and salt stress causes less damage to plants at the nutritional growth stage [59,60], the effect on fresh weight of MdNRT1.1 transgenic Arabidopsis may have been smaller (Figure 6C).…”
Section: Discussionmentioning
confidence: 99%